Kebijakan Pendidikan Islam di Era Transformasi Global - Dinar Sanjaya; Gilang Fajar; Irpan (JMPI: Jurnal Manajemen Pendidikan Islam, 2025)
This study examines Islamic education policies in the era of global transformation, focusing on the adaptation of educational institutions and government to the challenges of digitalization, globalization, and socio-cultural change. The research employs a qualitative approach using a literature study, reviewing various academic sources, policy documents, and previous studies. The findings indicate that Islamic education seeks to maintain a balance between mastery of religious knowledge, the strengthening of Islamic character, and the development of 21st-century competencies. Implemented strategies include the modernization of madrasahs through technology, capacity building for teachers, integration of religious and general curricula, and international collaboration. Future policies emphasize character-based education, expanded access through digitalization, and the enhancement of graduate competitiveness. These findings align with Diffusion of Innovation Theory and Transformational Learning Theory, highlighting adaptation to global changes and holistic development of learners.